From transaction marketing to relationship marketing a new perspective / Sharifah Zannierah Syed Marzuki and Wan Kalthom Yahya - Syed Marzuki, Sharifah Zannierah; Yahya, Wan Kalthom (2004)
Relationships do not function by themselves. It has been widely accepted as an important determinant of long-term business success and is believed to be especially well suited for services because of the personal contact between customers and service providers. To the seller a market is a collection of buyers and potential buyers some of whom can be attracted in to exchanges by tempting offers. The key to success in transaction marketing now lies with concentrating on and retaining existing customers. It can be describes that transaction marketing not only sells the products or services to the customers but also embracing them firmly at the centre. Customers are the judges of whatever products or services delivered to them. Thus, the marketers need to retain them and at the same time attracting the new ones. Basically there are some strategies that the sellers will do in extending their relationship with their precious and valued customers. Some of the examples are providing loyalty card, reward and privilege card, after sales service, sending updated information and messages through the Internet and even sending birthday cards. As markets mature, customer retention will become even more important. This is where marketing, customer service, quality programmes and operations take place and must be well co-ordinated. Relationship marketing has it all for bringing them together. It is certainly a new perspective which are more market-oriented and less manipulative and where the customer indeed is the focal point as suggested by the marketing concept. A firm that gives promises may attract new customers and initially build relationships. However, if premises are fragile and broken, the evolving relationship cannot be maintained and enhanced. Fulfilling promises is equally important as means of achieving customer satisfaction and retention. Marketers may say that it is a long-term investment to retain the customers in order for them to retain themselves in the marketplace.